Integrity moderation in village governance, professionalism and village financial accountability - Desyana Putri; Iskandar Muda; Keulana Erwin; Agung Wahyudhi Atmanegara (Institute of Accounting Research and Novation (IARN), 2026)
This study examines the effects of village governance and professionalism on village financial accountability and investigates the moderating role of integrity in strengthening these relationships. The research adopts a quantitative design using a survey method. Data were collected from 211 village governments in East Aceh Regency using purposive sampling. Questionnaires were used to measure the research variables, and data were analyzed using PLS SEM to test for direct and moderating effects. The novelty of this study lies in the development of a multidimensional village financial accountability model that integrates structural aspects (governance), competency (professionalism) and ethical (integrity) has not been widely explored in the literature on village government accountability. The results of the study indicate that village governance and professionalism have a positive and significant influence on village financial accountability. Moderation analysis indicates that the integrity of village officials can strengthen the influence of village governance and professionalism on village financial accountability. The study concludes that improving governance quality, strengthening professionalism, and fostering integrity simultaneously are essential strategies for enhancing village financial accountability. These findings provide theoretical implications in the development of a public sector accountability model based on local governance as well as practical implications for village governments in strengthening the capacity and professionalism of village officials to improve the quality of village financial accountability.